PENGEMBANGAN NILAI KARAKTER KONSERVASI BERBASIS PEMBELAJARAN - Ridlo, Saiful; Irsadi, Andin (Jurnal Penelitian Pendidikan, 2012)
Department of Biology, State University of Semarang (Unnes) is beeing committed to implement competency and conservation-based curriculum since the academic year 2012/2013. Character of the conservation values inculcated through integration in the learning process. This research problem is how to develop conservation based character education values. This research aims to generate value conservation character based learning of General Biology with a exploring environment (JAS) strategy. The research methodology uses a qualitative approach. As informants are faculty and students who teach and learn using competency and conservation-based curriculum for General Biology subjects. Data obtained in the form of descriptions of learning activities and interviews with informants. The data were analyzed later narrated. The results show the development of conservation-based character education values can begin of simple things that happen in the process of active and effective learning. Furthermore, teachers can pull things demonstrated by cognitive, affective and behavioral students of both positive and negative to the corresponding construct ten conservation value of character education.